Visible-Light-Promoted Asymmetric Catalysis by Chiral Complexes of First-Row Transition Metals - Li, Yanjun; Ye, Ziqi; Cai, Jiaxin; Gong, Lei (Synthesis, 2021)
This short review presents an overview of visible-light-driven asymmetric catalysis by chiral complexes of first-row transition metals. The processes described here include dual catalysis by a chiral complex of copper, nickel, cobalt, or chromium and an additional photoredox or energy-transfer catalyst, and bifunctional catalysis by a single chiral copper or nickel catalyst. These methods allow valuable transformations with high functional group compatibility. They provide stereoselective construction of carbon–carbon or carbon–heteroatom bonds under mild conditions, and produce a diverse range of previously unknown enantioenriched compounds.1 Introduction2 Nickel-Based Photocatalytic Asymmetric Catalysis3 Copper-Based Photocatalytic Asymmetric Catalysis4 Photocatalytic Asymmetric Catalysis by Chiral Complexes of Cobalt or Chromium5 Conclusion
Keywords: asymmetric photocatalysis; visible light; first-row transition metal; nickel; copper